“Ínterin dura este litigio no estoy obligado a pagar a Su Majestad.” Un caso de fraude en el asiento de pulque de Toluca, 1749-1756 - Galván Hernández, José Luis (El Colegio de México, A.C., 2025)
This article analyzes the procedural dimension of litigation over a debt by the Toluca pulque concession that was initiated in 1749. It emphasizes both the mechanisms employed by the royal officials of the Purse of Mexico to collect payment as well as those utilized by the debtor, Nicolás de Azoños, to resist collection and then go on to defraud his brother, neighbors and the authorities of the Royal Treasury in order to obtain a second five-year pulque concession while avoiding the corresponding payments. This article offers an approach to the way that the Treasury’s jurisdiction was exercised to prosecute concessionaires who refused to make the annual payments that had been negotiated with the tax authorities of New Spain.